"Como faço se depois fico sem dupla?": Afetividade e cognição de idosos com depressão em um jogo de tabuleiro moderno. - Barbosa, Anna Paula Sampaio (2019)
The psychological aspects related to aging and depression need to be further investigated due to the need of creating strategies of intervention in the context of the phenomenon of depression in elderly. This research aimed to investigate the elderly beha